The Dilemma of an Acting Regent's Authority in Civil Service Transfers: Between Bureaucratic Stability and the Prevention of Abuse of Power in Bondowoso Regency - Danang Maulana Almiansyah; Fauziyah Fauziyah (SS&H: Studies in Social Sciences and Humanities, 2026)
The filling of the position of Acting Regional Head during the transition period of simultaneous regional elections raises legal problems related to the limits of authority in the governance of State Civil Apparatus (ASN), especially in the policy of job transfers. This study aims to analyze the limits of the Acting Regent's authority in carrying out ASN transfers based on the Minister of Home Affairs Regulation Number 4 of 2023 and examine the legal implications of the implementation of transfers that do not comply with the provisions of laws and regulations. This study uses a normative legal research method with a statutory approach and a conceptual approach. The legal materials consist of primary, secondary, and tertiary legal materials which are analyzed descriptively qualitatively. The results of the study indicate that the Acting Regent's authority is a limited attribution authority and is subject to the principle of legality and the principle of the rule of law. In the context of ASN transfers, the Acting Regent is prohibited from carrying out transfers without the written approval of the Minister of Home Affairs as regulated in Article 15 paragraph (2) of the Minister of Home Affairs Regulation Number 4 of 2023. These restrictions are intended to maintain the neutrality of ASN, prevent the politicization of bureaucracy, and ensure the stability of regional government during the political transition period. Implementing ASN transfers without the approval of the Minister of Home Affairs results in a defect in authority (detournement de pouvoir), which can potentially invalidate or overturn administrative decisions. A case study of official transfers in Bondowoso Regency demonstrates the importance of adhering to administrative procedures and limiting authority to ensure legal certainty and good governance.